Epigenetic Effects of Gut Metabolites: Exploring the Path of Dietary Prevention of Type 1 Diabetes - Al Theyab, Ahmad; Almutairi, Turki; Al-Suwaidi, Abdulla M.; Bendriss, Ghizlane; McVeigh, Clare; Chaari, Ali (Frontiers in Nutrition, 2020)
Type 1 diabetes (T1D) has increased over the past half century and has now become the second most frequent autoimmune disease in childhood and one of major public health concern worldwide. Evidence suggests that modern lifestyles and rapid environmental changes are driving factors that underlie this increase. The integration of these two factors bring about changes in food intake. This, in turn, alters epigenetic regulations of the genome and intestinal microbiota composition which may ultimately play a role in pathogenesis of T1D. Recent evidence shows that dysbiosis of the gut microbiota is highly associated with T1D and that a dietary intervention can influence epigenetic changes associated with this disease and may modify gene expression patterns through epigenetic mechanisms. In this review, we will focus on how a diet can shape the gut microbiome, its effect on the epigenome in T1D and the future of T1D management by microbiome therapy.